The Strategic Exercise of Options: Development Cascades and Overbuilding in Real Estate Markets - GRENADIER, STEVEN R. (Journal of Finance, 1996)
ABSTRACT This article develops an equilibrium framework for strategic option exercise games. I focus on a particular example: the timing of real estate development. An analysis of the equilibrium exercise policies of developers provides insights into the forces that shape market behavior. The model isolates the factors that make some markets prone to bursts of concentrated development. The model also provides an explanation for why some markets may experience building booms in the face of declining demand and property values. While such behavior is often regarded as irrational overbuilding, the model provides a rational foundation for such exercise patterns.